The validity and reliability of the Incremental Shuttle Walk Test and Six-minute Walk Test compared to an Incremental Cycle Test for people who have had a mild-to-moderate stroke. Issue 2 (June 2019) - Clague-Baker, Nicola; Robinson, Thompson; Hagenberg, Annegret; Drewry, Sophie; Gillies, Clare; Singh, Sally
Abstract: Objective: To determine the construct validity and test re-test reliability of the Six-minute Walk Test (6MWT) and Incremental Shuttle Walk Test (ISWT) in the sub-acute recovery phase following mild-to-moderate severity stroke. Participants: 40 stroke patients (mean age: 68.27 years, SD: 13.48) of median National Institutes of Health Stroke Scale (NIHSS) score 1.2 (range: 0 to 8) within six months of stroke. Method: Each participant completed one Incremental Cycle Test (ICT) followed by two ISWT and two 6MWT in a randomised order. Pearson's Correlation Coefficients were used to determine the validity and Bland Altman plots were used to determine the test re-test reliability. Results: The Incremental Cycle Test (ICT) was positively correlated with the ISWT (r = 0.59, 95% confidence intervals 0.35 to 0.76, P = 0.001) and the 6MWT (0.55, 0.35 to 0.71, P < 0.001). The correlation of the ICT with the ISWT and 6MWT was higher for the 17 patients with no residual (ISWT: r = 0.79, P < 0.001; 6MWT: 0.826, P < 0.001) compared to mild-to-moderate neurological impairment (ISWT: r = 0.45, P = 0.03; 6MWT: r = 0.38, P = 0.08). Test–retest reliability for both the ISWT and the 6MWT showed that there was some variability between the first and second tests with a better performance on the second test. Conclusion: The ISWT and 6MWT have a significant, modest correlation with the ICT for stroke patients in the sub-acute recovery phase. The ISWT and 6MWT are not strongly correlated with ICT (VO2 peak) in a stroke population that is disabled. The test–retest reliability of the ISWT and 6MWT indicated that two tests may be needed to accurately assess an individual's capabilities.